SOCIAL MEDIA ANALYSIS AND SERVICE INNOVATION ON SATISFACTION WITH TRUST AS AN INTERVENING VARIABLE AT THE POPULATION SERVICE AND CIVIL REGISTRATION OFFICE OF MEDAN CITY - Lusianna Banurea; Mesra B; Elfitra Desy Surya (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Digital transformation encourages public service agencies to optimize social media and service innovation to improve satisfaction by strengthening trust. This study analyzes the influence of social media and service innovation on public satisfaction with trust as an intervening variable at the Population and Civil Registration Office of Medan City. The method used is quantitative with a sample of 98 respondents (service users in the last 12 months). Primary data were collected through questionnaires and analyzed using PLS-SEM (SmartPLS). The instruments met the requirements for convergent validity (outer loadings ≥ 0.60; AVE ≥ 0.552) and reliability (Cronbach's Alpha ≥ 0.723; CR ≥ 0.829). The results show that social media has a positive and significant effect on satisfaction (β=0.254; p=0.005) and trust (β=0.155; p=0.049). Service innovation has a positive but insignificant effect on satisfaction (β=0.120; p=0.175), but a positive and significant effect on trust (β=0.490; p=0.000). Trust has a positive and significant effect on satisfaction (β=0.324; p=0.000). The mediation test shows that social media → trust → satisfaction is not significant (p=0.113), while service innovation → trust → satisfaction is significant (p=0.005). The explanatory power of the model is strong (R² trust=0.705; R² satisfaction=0.889). Practical implications: strengthening social media content and responses needs to be accompanied by innovations that increase trust—such as process transparency, real-time status tracking, and SLA standards—in order to have a direct impact on satisfaction.